Isolation, characterisation and antioxidant activity of bioactive ingredients of Cissus Discolor Blume - Ma, Hnin Hnin Aung (2008)
Chapter one of this report introduces the active substances of medicinal plants and antioxidant activities of flavonoids. Chapter two outlines free radical generation and antioxidant defense system in our body. Chapter three introduces the phenomena of electron spin resonance. Then, analytical methods used to determine the antioxidant ability by UV and ESR methods are discussed in chapter four. A lot of data achieved by screening work and time-consuming experiments are listed in chapter five. These data mainly concern the antioxidant activities in different extracts and fractions of the medicinal plant CD. Chapter six summaries the major findings of this study and recommend some possible areas for further research.